Bacteriological studies of the venom and mouth cavities of wild Malayan pit vipers (Calloselasma rhodostoma) in southern Thailand. - Theakston, R; Phillips, R; Looareesuwan, S; Echeverria, P; Makin, T; Warrell, D (1990)
Venom and oropharyngeal swabs from freshly captured Malayan pit vipers (Calloselasma rhodostoma) in southern Thailand and captive specimens in England were cultured aerobically and anaerobically to identify the bacterial flora which might contaminate wounds inflicted by bites of this species. The snakes' mouths contained a wider range of organisms than their venoms, especially gut-related Gram-negative rods such as Enterobacter and Pseudomonas species and some staphylococci and clostridia. There were fewer positive cultures from captive snakes. C. rhodostoma venom inhibited the growth of group A streptococci and, to a lesser extent, that of Staphylococcus aureus and Clostridium perfringens but not that of 2 Gram-negative organisms. Secondary bacterial infection is an important complication of snake bite, especially of necrotic wounds. A combination of gentamicin with benzyl penicillin would have prevented infection with, or treated, most of the bacteria isolated from snake venoms and mouths in Thailand.